2018
DOI: 10.1177/1055665618796018
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Perceived Barriers to Accessing Cleft Care at a Tertiary Referral Center in São Paulo, Brazil

Abstract: Delays from diagnosis to treatment result in patients receiving delayed primary repairs. The commonest patient-perceived barriers are related to a lack of access to cleft care, which may represent a lack of awareness of available services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 18 publications
4
28
0
1
Order By: Relevance
“…These findings are similar to a 2009 retrospective cohort study in North Carolina by Cassell et al in which 42.0% of children with CP were delayed for repair beyond 18 months of age (Cassell et al, 2009). In our overall cohort, 79.5% of children undergoing CP repair had a diagnosis of isolated CP, a more inconspicuous defect compared to CLP that can be more difficult to detect by referring physicians without proper training (Habel et al, 2006; Ise et al, 2019;). More specifically, incomplete CP especially isolated clefts of the soft palate can be more difficult to detect on digital inspection alone and may require additional visual inspection (Habel et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings are similar to a 2009 retrospective cohort study in North Carolina by Cassell et al in which 42.0% of children with CP were delayed for repair beyond 18 months of age (Cassell et al, 2009). In our overall cohort, 79.5% of children undergoing CP repair had a diagnosis of isolated CP, a more inconspicuous defect compared to CLP that can be more difficult to detect by referring physicians without proper training (Habel et al, 2006; Ise et al, 2019;). More specifically, incomplete CP especially isolated clefts of the soft palate can be more difficult to detect on digital inspection alone and may require additional visual inspection (Habel et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Despite these standards, multiple barriers to care can impede timely CL/P diagnosis, surgical repair, follow-up, and further interventions. Availability of surgeons can serve as a significant obstacle (Carlson et al, 2016b), and challenges such as financial cost, geographic accessibility, education, or cultural understanding of surgical need also may delay care (Adetayo et al, 2012; Cassell et al, 2013; Cassell et al, 2014; Massenburg et al, 2016; Yao et al, 2016; Carlson et al, 2016b; Swanson et al, 2017; Bennett et al, 2018; Dean et al, 2019; Ise et al, 2019; Kantar et al, 2019; Stock et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Al respecto, uno de los pocos estudios publicados sobre distancias y tiempos hasta los centros de atención de FLAP en Estados unidos, encontró que los padres no consideraban las largas distancias como "un problema", aunque ese trabajo no valoró las características o los resultados de los tratamientos recibidos 33 . Otro estudio analizó las barreras al tratamiento percibidas por los padres encontrando que quienes mencionaron que era muy costoso el traslado hasta el centro tratante tenían más chance de haber realizado la cirugía tardíamente 34 .…”
Section: Discussionunclassified
“…This has also been observed in other regions of the country. A study by Ise et al (2019), conducted in Southeast Brazil, found that 54% of individuals underwent primary lip and palate repair later than recommended in the literature, concluding that the main barriers for the access of treatment were lack of available hospitals for surgery (54%) and lack of surgeons (51%).…”
Section: Discussionmentioning
confidence: 99%
“…According to the standardized treatment protocol in Brazil, primary lip surgery should be performed at around 3 months of age and palatoplasty at 12 months (Bertier et al, 2007). Studies conducted in developing countries concluded that patients living in remote areas with difficult access to health units receive treatment late and face several main barriers, such as lack of information, travel costs, lack of hospitals to perform surgery, and lack of financial support (Massenburg et al, 2016; Ise et al, 2019). In the Amazon region, specifically Northern Brazil, these difficulties are further complicated by the climate and geographic characteristics typical of the region, making it one of the main areas of the country with a scarcity of specialized health services.…”
Section: Introductionmentioning
confidence: 99%